Discovery of plasma proteome markers associated with clinical outcome and immunological stress after cardiac surgery - Bello, Corina; Filipovic, Mark G.; Huber, Markus; Flannery, Sarah; Kobel, Beatrice; Fischer, Roman; Kessler, Benedikt M.; Räber, Lorenz; Stueber, Frank; Luedi, Markus M. (Frontiers in Cardiovascular Medicine, 2023)
Molecular mechanisms underlying perioperative acute phase reactions in cardiac surgery are largely unknown. We aimed to characterise perioperative alterations of the acute phase plasma proteome in a cohort of adult patients undergoing on-pump cardiac surgery using high-throughput mass spectrometry and to identify candidate proteins potentially relevant to postoperative clinical outcome through a novel, multi-step approach. Methods: This study is an analysis of the Bern perioperative Biobank, a prospective cohort of adults who underwent cardiac surgery with the use of cardiopulmonary bypass (CPB) at Bern University Hospital between January and December 2019. Blood samples were taken before induction of anaesthesia and on postoperative day one. Proteomic analyses were performed by mass spectrometry. Through a multistep, exploratory approach, hit-proteins were first identified according to their perioperative prevalence and dynamics. The set of hit-proteins were associated with predefined clinical outcome measures (allcause one-year mortality, length of hospital stay, postoperative myocardial infarction and stroke until hospital discharge).192 patients (75.5% male, median age 67.0 [IQR 60.0 -73.0]) undergoing cardiac surgery with the use of CPB were included in this analysis. In total, we identified and quantified 402 proteins across all samples, whereof 30/402 (7%) proteins were identified as hit-proteins. Four hit-proteins -SERPINA1, LDHB, VCAM1 and IGFBP2demonstrated the strongest associations with clinical outcomes. After adjustment both for age, sex, BMI and for multiple comparisons, the scaled preoperative levels of IGFBP2 were associated with 1-year all-cause mortality (OR 10.28; 95%CI: 3.01 -52.65; p = 0.031). Additionally, scaled preoperative levels of LDHB (OR 5.58; 95%CI: 2.58 -8.57; p = 0.009) and VCAM1 (OR 2.23; 95%CI: 0.88 -3.77; p = 0.002) were found to be associated with length of hospital stay.We identified a subset of promising candidate plasma proteins relevant to outcome after on-pump cardiac surgery. IGFBP2 showed a strong association with clinical outcome measures and a significant association of preoperative levels with 1-year all-cause mortality. Other proteins strongly associated with outcome were LDHB, VCAM1 and SERPINA1, reflecting the dynamics in the acute phase response, inflammation and myocardial injury. We recommend further investigation of these proteins as potential outcome markers after cardiac surgery.